Current survival measures reliably reflect modern sequential treatment in CML: Correlation with prognostic stratifications. Issue 9 (23rd July 2013) - Pavlik, Tomas; Janousova, Eva; Mayer, Jiri; Indrak, Karel; Jarosova, Marie; Klamova, Hana; Zackova, Daniela; Voglova, Jaroslava; Faber, Edgar; Karas, Michal; Machova Polakova, Katerina; Racil, Zdenek; et al.
<x xml:space="preserve">Abstract</x> Using the data of 723 chronic myeloid leukemia (CML) patients in the chronic phase, we analyzed the prognostic value of the Sokal, Euro, and EUTOS scores as well as the level of BCR‐ABL1 and the achievement of complete cytogenetic response (CCgR) at 3 months of imatinib therapy in relation to the so‐called current survival measures: the current cumulative incidence (CCI) reflecting the probability of being alive and in CCgR after starting imatinib therapy; the current leukemia‐free survival (CLFS) reflecting the probability of being alive and in CCgR after achieving the first CCgR; and the overall survival. The greatest difference between the CCI curves at 5 years after initiating imatinib therapy was observed for the BCR‐ABL1 transcripts at 3 months. The 5‐year CCI was 94.3% in patients with BCR‐ABL1 transcripts ≤ 10% and 57.1% in patients with BCR‐ABL1 transcripts > 10% (P = 0.005). Therefore, the examination of BCR‐ABL1 transcripts at 3 months may help in early identification of patients who are likely to perform poorly with imatinib. On the other hand, CLFS was not significantly affected by the considered stratifications. In conclusion, our results indicate that once the CCgR is achieved, the prognosis is good irrespective of the starting prognostic risks. Am. J. Hematol. 88:790–797, 2013. © 2013 Wiley Periodicals, Inc.